Design and Fabrication of a Single-Stage U-Type Savonius Wind Turbine Using Low Wind Speeds and Water Hyacinth Composite Material - Suheri Suheri; Syamsul Bahri Widodo; Zainal Arif; Iskandar Yacob; Muhammad Syafii (JURUTERA - Jurnal Umum Teknik Terapan, 2024)
This research created an innovative single-stage U-type Savonius wind turbine with water hyacinth composite material, intended for low wind speeds. With the steps of wind speed measurement, turbine rotation monitoring, and power measurement, interesting results such as a wind speed of 4.52 m/s producing a power of 5.17 volts were revealed. The significance lies in the potential of the water hyacinth composite turbine in utilizing low wind speeds to generate electricity. The conclusion notes the achievements in the manufacturing process of Savonius turbine blades and suggests that these findings provide an important basis for the development of composite-based wind turbines as an environmentally friendly renewable energy source.